Pengembangan Sistem Antrean Berbasis Android pada Layanan Administrasi di Universitas Teknologi Yogyakarta - Ahmad Syaiful; Muhammad Fachrie (Komputika : Jurnal Sistem Komputer, 2020)
The length of the queue at a service provider counter certainly makes the service users uncomfortable, bored, and even tired while waiting. In addition, too much time is wasted while waiting in line. The uncertainty of time in waiting their turn often causes problems for service users which often results in no service to some users because the service hours are over. This also happened to several administrative services at Universitas Teknologi Yogyakarta, where students had to queue long at bank counters on campus or in the Finance Department counters just to pay tuition fees or validate payments. Therefore, in this article, we discuss the development of Android-based applications that serve to assist service providers in managing queues, as well as making it easier for queues to retrieve queue numbers and get an estimated time to wait their turn to get service. The application was developed using Android Studio by utilizing Google's Firebase database to support the ease of application development. To measure the appropriateness of application use, tests on several different devices have also been carried out.